Post harvest treatment of citrus supplier bud branches - Carvalho, Sérgio Alves de; Sandrini, Márcio; Tavares, Edson Diogo; Silva, Luiz Fernando C. da; Rocha, Aledir Cassiano da (Pesquisa Agropecuaria Brasileira, 2014)
The phytophagous mites, one of the most harmful citrus pests, cause great losses in several countries. In Brazil, the most harmful ones are the citrus rust mite (Phyllocoptruta oleivora), the leprosis mite (Brevipalpus phoenicis) and the citrus bud mite (Eriophyes sheldoni). The viability of control of these mites thought the supplier bud branches treatment was studied in this work. Among the products tested, Bynapacril at 0.2% was the single with 100% control.